A-type lamins maintain the positional stability of DNA damage repair foci in mammalian nuclei. - Robert Mahen; Hiroyoshi Hattori; Miyoung Lee; Pooja Sharma; Anand D Jeyasekharan; Ashok R Venkitaraman (PLoS ONE)
A-type lamins encoded by LMNA form a structural fibrillar meshwork within the mammalian nucleus. How this nuclear organization may influence the execution of biological processes involving DNA transactions remains unclear. Here, we characterize changes in the dynamics and biochemical interactions of lamin A/C after DNA damage. We find that DNA breakage reduces the mobility of nucleoplasmic GFP-lamin A throughout the nucleus as measured by dynamic fluorescence imaging and spectroscopy in living cells, suggestive of incorporation into stable macromolecular complexes, but does not induce the focal accumulation of GFP-lamin A at damage sites. Using a proximity ligation assay and biochemical analyses, we show that lamin A engages chromatin via histone H2AX and its phosphorylated form (γH2AX) induced by DNA damage, and that these interactions are enhanced after DNA damage. Finally, we use three-dimensional time-lapse imaging to show that LMNA inactivation significantly reduces the positional stability of DNA repair foci in living cells. This defect is partially rescued by the stable expression of GFP-lamin A. Thus collectively, our findings suggest that the dynamic structural meshwork formed by A-type lamins anchors sites of DNA repair in mammalian nuclei, providing fresh insight into the control of DNA transactions by nuclear structural organization.